Management of a large splenic hydatid cyst in pregnancy: A case report - Adeleena Mazid; Johannes De Kock (Elsevier, 2024)
Splenic hydatid cysts are caused by the Echinococcus species and rarely occur in pregnancy. This case report describes the management of a 29-year-old pregnant woman with a large (11 × 8.7 × 10.5 cm) splenic hydatid cyst. The cyst had been identified before she became pregnant by her general practitioner with imaging investigations undertaken for her persistent left upper abdominal pain. The patient also had laboratory investigations which were positive for echinococcosis species.Hydatid splenic cysts are very rare and even more so in pregnancy. Risk of splenic cyst rupture exists, and rupture has significant risk of maternal and perinatal morbidity and mortality. Among the few case reports in the literature there is no clear consensus on conservative or surgical management during pregnancy and no clear guidelines for intrapartum care or delivery. The case report reviews the literature on splenic hydatid cyst disease in pregnancy and explores the management and outcome of this patient through her fourth pregnancy, which resulted in an uncomplicated vaginal birth.